Carotenogênese em células de Haematococcus pluvialis induzidas pelos estresses luminoso e nutricional - Nunes, Moira [UNESP]; Vieira, Armando Augusto Henriques; Pinto, Ernani; Carneiro, Ronaldo Leal; Monteiro, Antonio Carlos [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2013)
The objective of this work was to evaluate the responses of Haematococcus pluvialis cells to the carotenogenesis induction process, under light and nutrition stress. Cells were acclimated during 15 days in WC medium, with aeration with synthetic, filtered atmospheric air and flow rate of 100 mL min-1, light intensity of 50 µmol photons m-2 s-1, photoperiod of 12 hours, and temperature of 23ºC. The following two treatments were compared: cultivation under the described conditions, but with increase of light intensity up to 350 µmol photons m-2 s-1 ; and cultivation under the same conditions as the previous treatment, but with aeration containing 4% CO2. The treatments were done in triplicate, during ten days. With the addition of CO2 and the increment in lighting, an increase was observed in the carotenoids/chlorophyll ratio and cell biomass. Cells stopped dividing on the second day of stress, when nitrate became limiting, and significantly increased their biovolume. The excretion of organic carbon and the concentration of astaxanthin increase in response to the addition of CO2. Stress by light intensity combined with CO2 addition optimizes carotenogenesis in H. pluvialis and increases astaxanthin production.

O objetivo deste trabalho foi avaliar as respostas das células de Haematococcus pluvialis ao processo de indução à carotenogênese, sob estresse luminoso e nutricional. As células foram aclimatadas durante 15 dias em meio WC, com aeração com ar atmosférico sintético filtrado e fluxo de 100 mL min-1, intensidade luminosa de 50 µmol fótons m-2 s-1, fotoperíodo de 12 horas e temperatura de 23ºC. Foram comparados dois tratamentos: cultivo nas condições descritas, mas com aumento da intensidade luminosa para 350 µmol fótons m-2 s-1 ; e cultivo nas mesmas condições do tratamento anterior, mas com aeração contendo 4% de CO2. Os tratamentos foram conduzidos em triplicata, durante dez dias. Com a adição de CO2 e o incremento da iluminação, observou-se aumento da razão carotenoides/clorofila e da biomassa celular. As células cessaram a divisão no segundo dia de estresse, quando o nitrato se tornou limitante, e aumentaram significativamente seu biovolume. A excreção de carbono orgânico e a concentração de astaxantina aumentam em resposta à adição de CO2. O estresse por intensidade luminosa, aliado à adição de CO2, otimiza a carotenogênese em H. pluvialis e aumenta a produção de astaxantina.
Carotenogenesis in Haematococcus pluvialis cells induced by light and nutrient stresses
Keywords: astaxanthin; dissolved organic carbon; carotenoid; Light intensity; microalga; astaxantina; carbono orgânico dissolvido; carotenoide; Intensidade luminosa; Microalga